Utilization of Social Media by Female Legislative Candidates for Healthy Campaigns - Rosidin, Rosidin; Kurniawati, Juliana; Heriyanti, Lesty (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Social media is currently seen as a very effective medium to use in campaigns. Apart from its low cost, social media is also used by many people on this earth, including in Bengkulu. A healthy campaign is a very noble thing and has high moral value. To get sympathy from voters you don't have to carry out smear campaigns or character assassination. However, it can be done well, with full openness and transparency. The research method used is a qualitative descriptive method. Data collection techniques use observation, interview and documentation techniques. Researchers conducted searches on social media used by DPD RI Women candidates. Data on what media are used by female DPD RI candidates. The research results reveal that in general the social media used are Instagram, Facebook and Tiktok. The amount of content and content content for each candidate is similar. The content is adjusted to the situation and conditions currently occurring at that time. Social media platforms are considered to be a very effective campaign tool that can increase the popularity and electability of candidates. Not a single piece of content was found used by the DPD RI Female Member Candidates for the Electoral District of Bengkulu Province which contained SARA content, black campaigning and defamation as well as cornering each other. candidate. This means that the DPD RI Women's Legislative Candidates have carried out a healthy campaign